True and false left ventricular aneurysm Combination: case report - Levchyshyna, O. V.; Beshlyaga, V. M.; Rudenko, A. V. (Ukrainian Journal of Cardiovascular Surgery, 2019)
The article presents a case report of diagnosis and surgical treatment of a true and false left ventricular aneurysm combination in a patient after acute myocardial infarction. The patient K. was admitted to the clinic with a diagnosis of coronary heart disease. Echocardiography revealed aneurysm of the posterior wall of the left ventricle. An additional cavity was visualized behind the posterior wall of the left ventricle. Emergency coronaroventriculography was performed in this patient. The left coronary artery angiogram revealed moderate (up to 50%) stenoses of the middle third of circumflex artery, anterior interventricular artery, diagonal branch of the left coronary artery. The right coronary artery angiogram revealed occlusion of the distal third of the artery. The left ventriculography showed that the left ventricle cavity is significantly deformed, the wall contractility is reduced, and there is aneurysm in the left ventricle. Due to the threat of tamponade, emergency resection of the posterior-lateral left ventricular aneurysm was performed. According to the echocardiography, after the intervention, deformation of the left ventricle cavity was absent, the mitral valve was preserved, the contractility improved. The patient was transferred to a cardiac hospital at the place of residence. Accurate diagnosis and urgent surgical treatment helped to patient not only to survive but also to maintain the quality of life.